Maize Genotypes With Different Zinc Efficiency in Response to Low Zinc Stress and Heterogeneous Zinc Supply - Xu, Jianqin; Wang, Xuejie; Zhu, Huaqing; Yu, Futong (Frontiers in Plant Science, 2021)
All over the world, a common problem in the soil is the low content of available zinc which is unevenly distributed and difficult to move. However, information on the foraging strategies of roots in response to heterogeneous zinc supply is still very limited. And few studies have analyzed the adaptability of maize inbred lines with different zinc efficiency to different length of zinc starvation time in maize. This study analyzed the effects of different time lengths of low zinc stress on various related traits in different inbred lines. And morphological plasticity of roots and the response of zinc-related important genes ZIPs were studied via simulating the heterogeneity of zinc nutrition in the soil. In this report, when zinc deficiency stress duration was extended (from 14 days to 21 days), under Zn-deficient supply (0.5 μM), zinc efficiency (ZE) based on shoot dry weight of Wu312 display no significant difference, and ZE for Ye478 was increased by 92.9%. Under longer-term zinc deficiency, shoot and root dry weights of Ye478 were 6.5-fold and 2.1-fold higher than those of Wu312, respectively. Uneven zinc supply strongly inhibited the development of some root traits in the -Zn region. Difference in shoot dry weights between Wu312 and Ye478 was larger in T1 (1.97 times) than in T2 (1.53 times). Under heterogeneous condition of zinc supply, both the -Zn region and the +Zn region up-regulated the expressions of ZmZIP3, ZmZIP4, ZmZIP5, ZmZIP7, and ZmZIP8 in the roots of two inbred lines. These results indicate that extended time length of low-zinc stress will enlarge the difference of multiple physiological traits, especially biomass, between zinc-sensitive and zinc-tolerant inbred lines. There were significant genotypic differences of root morphology in response to heterogeneous zinc supply. And compared under split-supply with +Zn/+Zn, the difference of above-ground biomass under split-supply with -Zn/+Zn between different inbred lines increased. Under the condition of heterogeneous zinc supply, several ZmZIP genes may play an important role in tolerance to low zinc stress, which can provide a basis for further functional characterization.